2005
DOI: 10.1111/j.1944-9720.2005.tb02517.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prelistening Activities on Listening Comprehension in Arabic Learners

Abstract: This study evaluated the effect of prelistening activities and repeated listening exposure on listening comprehension scores of Arabic students. Participants completed a prelistening activity (vocabulary preview or question preview) or a distracter activity (Arabic verb conjugation), listened to an Arabic listening passage, and took a listening comprehension test. Participants listened to the passage again and repeated the test. Students who completed either prelistening activity scored higher than those who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 36 publications
5
30
0
Order By: Relevance
“…L2 captions can be useful (e.g., Markham, Peter, & McCarthy, 2001) as well as pictorial support and written annotations (Jones & Plass, 2002) and digital stories (Verdugo & Belmonte, 2007). Methods fostering bottom‐up processing such as adjusting the speech rate (Zhao, 1997), repeating the oral text (e.g., Elkafaifi, 2005; Jensen & Vinther, 2003; Zhao, 1997), providing L2 subtitles (Stewart & Pertusa, 2004), and attending to prosodic features (Harley, 2000) have also met with success. This body of research has demonstrated that L2 learners can be taught to use a number of cues to facilitate their comprehension of oral texts.…”
Section: Research On Facilitating L2 Listeningmentioning
confidence: 99%
“…L2 captions can be useful (e.g., Markham, Peter, & McCarthy, 2001) as well as pictorial support and written annotations (Jones & Plass, 2002) and digital stories (Verdugo & Belmonte, 2007). Methods fostering bottom‐up processing such as adjusting the speech rate (Zhao, 1997), repeating the oral text (e.g., Elkafaifi, 2005; Jensen & Vinther, 2003; Zhao, 1997), providing L2 subtitles (Stewart & Pertusa, 2004), and attending to prosodic features (Harley, 2000) have also met with success. This body of research has demonstrated that L2 learners can be taught to use a number of cues to facilitate their comprehension of oral texts.…”
Section: Research On Facilitating L2 Listeningmentioning
confidence: 99%
“…Research has revealed that multiple exposures to a listening text generally aid its comprehension (Field, 2002;Elkhafaifi, 2008). This mediational strategy consists of two sub-strategies: 1) listening to the entire portion, and 2) listening to a segment from the portion, the latter being more explicit than the former in that it provides more assistance by narrowing the learners' focus to the part, where they had some misunderstandings.…”
Section: Figure 1 Typology Of Mediational Strategiesmentioning
confidence: 99%
“…Listeners listened twice and then wrote down what they could remember about the story in Group D. The outcome showed that group C performed better than other groups did. Elkhafaifi (2005) conducted research into the influence of different pre-listening supports. Participants performed a pre-listening activity (vocabulary preview or question preview) or a distractor activity (Arabic verb conjugation, they listened to an Arabic listening passage) and took a listening comprehension test.…”
Section: Literature Reviewmentioning
confidence: 99%